Influence of Degree of Hydrolysis on Chemical Composition, Functional Properties, and Antioxidant Activities of Chinese Sturgeon (Acipenser sinensis) Hydrolysates Obtained by Using Alcalase 2.4L. Issue 6 (3rd July 2019) - Noman, Anwar; Qixing, Jiang; Xu, Yanshun; Ali, Abdelmoneim H.; Al-Bukhaiti, Wedad Q.; Abed, Sherif M.; Xia, Wenshui
ABSTRACT: Protein hydrolysates from Chinese sturgeon were prepared using Alcalase 2.4L enzyme. Under the optimum conditions (enzyme–substrate ratio of 3.5%, pH of 8.5, and temperature of 55°C), the degree of hydrolysis (DH) was 13.8%, 16.7%, and 19.1% after 1, 3, and 6 h, respectively. The contents of crude protein and amino acid increased at DH of 19.1% to 86.97% and 78.29%, respectively. There was an obvious increase in the low-molecular-weight peptides, which could enhance the hydrolysate's functional properties such as solubility, representing more than 90% at different pH levels. The obtained protein hydrolysates revealed good emulsification properties and high oil absorption. Furthermore, good antioxidant activities such as 1, 1-diphenyl-2-picrylhydrazyl (DPPH) inhibition, ferric reducing power, and ferrous ion (Fe 2+) chelating ability were attained depending on the solution concentration. The findings indicate that the functional and antioxidant properties of protein hydrolysates could be useful in many applications of the food industry.